A wearable tracking device inkjet-printed on textile. (July 2017) - Krykpayev, Bauyrzhan; Farooqui, Muhammad Fahad; Bilal, Rana Muhammad; Vaseem, Mohammad; Shamim, Atif
Abstract: Despite the abundance of localization applications, the tracking devices have never been truly realized in E-textiles. Standard printed circuit board (PCB)-based devices are obtrusive and rigid and hence not suitable for textile based implementations. An attractive option would be direct printing of circuit layout on the textile itself, negating the use of rigid PCB materials. However, high surface roughness and porosity of textiles prevents efficient and reliable printing of electronics on textile. In this work, by printing an interface layer on the textile first, a complete localization circuit integrated with an antenna has been inkjet-printed on the textile for the first time. Printed conductive traces were optimized in terms of conductivity and resolution by controlling the number of over-printed layers. The tracking device determines the wearer's position using WiFi and this information can be displayed on any internet-enabled device, such as smart phone. The device is compact (55 mm×45 mm) and lightweight (22 g with 500 mAh battery) for people to comfortably wear it and can be easily concealed in case discretion is required. The device operates at 2.4 GHz communicated up to a distance of 55 m, with localization accuracy of up to 8 m.